A new species of Passiflora (subgenus Passiflora, Passifloraceae) from Bahia, Brazil - Imig, Daniela Cristina [UNESP]; Amano, Érika (Wiley, 2020)
A new species of Passiflora subgenus Passiflora from the Brazilian flora is described and illustrated in this article. Passiflora faleiroi was collected in Prado, state of Bahia, and belongs to the supersection Stipulata, section Granadillastrum. Passiflora faleiroi is compared to two similar species, P. mucronata Lam. and P. silvestris Vell.
Keywords: P. sect. Stipulata; Passion flowers; Section Granadillastrum; taxonomy; vines